An educational intervention study on mandatory reporting of intimate partner violence: changes in knowledge and attitudes among healthcare providers - Thea Beate Brevik; Petter Laake; Stål Bjørkly; Kjartan Leer-Salvesen; Solveig Karin Bø Vatnar (BMC Medical Education)
Abstract Background Intimate partner violence (IPV) is a major public health concern. Healthcare providers can play a crucial role in reporting cases of IPV or suspected IPV injuries to the police or the criminal justice system, commonly referred to as mandatory reporting. However, mandatory reporting of intimate partner violence (MR-IPV) is a debated topic that can pose complex challenges for healthcare providers. This underscores the importance of training programs to ensure that healthcare providers can fulfill their MR-IPV obligations. Methods We developed an educational intervention on MR-IPV and assessed its impact on healthcare providers’ knowledge and attitudes. The study used a pre- and post-test design with three measurement points: baseline (T0), immediately after the intervention (T1), and six months later (T2). The intervention was conducted at a university college in Norway, with data collected between October 2022 and May 2023. The intervention was delivered to 37 healthcare providers who were currently part-time students in mental healthcare. Changes in knowledge and attitudes between T0 and T1, and T0 and T2 were analyzed through nonparametric tests on related samples using the Marginal homogeneity (Stuart–Maxwell) test. Risk differences (RD), along with their corresponding 95% confidence intervals (CI), were calculated for selected categories. Results The number of participants knowing the MR law increased from 2.9% at baseline to 62.9% at T1 (RD = 0.60, 95% CI: 0.41—0.79) and to 31.4% at T2 (RD = 0.29, 95% CI: 0.11–0.46). The number of participants reporting knowing relevant criteria increased from 0.0% at baseline to 68.6% at T1 (RD = 0.69, 95% CI: 0.50–0.87) and to 34.3% at T2 (RD = 0.34, 95% CI: 0.16—0.53). We observed several persistent changes in healthcare providers' attitudes towards MR, including finding MR to be a useful instrument and generally complying with MR requirements. Conclusions The findings suggest that this educational intervention can have a positive impact on healthcare providers' attitudes and compliance with MR-IPV. Before the intervention, few participants reported knowing the MR law and its application criteria, demonstrating the importance of continuous learning and evidence-based training programs.